STUDENTS’ PERCEPTION ON THE USE OF QUIZIZZ IN LEARNING ENGLISH AT SMP ISLAM AS – SHOFA PEKANBARU - Tesa Untari; Syofia Delfi; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research aimed to find out how the perceptions of SMPS As-Shofa students on using Quizizz Application in learning English. The sample of this research was taken by using the total sampling technique that from ninth grade students of SMPS As-Shofa Pekanbaru. The number of samples was 55 students. The data was collected by using a questionnaire. There are 35 questions in total in the questionnaire, specify the type of questionnaire that will be used in this research. To be specific, the pre-defined responses that used in this research are in the type of rating scale: from strongly agree to strongly disagree, with neutral in the middle of the defined responses, although close-ended questionnaire gives limited insight and information, it still can be easily analyzed for quantitative data. The result of this research, SMPS students have the perception that Quizizz helps learn English very well, were feel easy, satisfied, motivated, indicating cognitive and affective results, are a bit challenged and practical in the process of learning English, There are some things that are unsatisfactory such as students still distracted by gadgets, still feeling afraid of English courses, and feeling a little anxious. Based on the study, students are recommended to use Quizizz in learning English in the class because it helps them to engaged in the online quiz in a convenient way in the English class.Key Words: Students’ Perception, Quizizz, Application, English Learning